COVID-19 patients display changes in lymphocyte subsets with a higher frequency of dysfunctional CD8lo T cells associated with disease severity - Onofrio, Luisina Ines; Marin, Constanza; Dutto, Jeremías; Brugo, María Belén; Baigorri, Ruth Eliana; Bossio, Sabrina Noemi; Quiróz, Juan Nahuel; Almada, Laura; Ruiz Moreno, Federico; Olivera, Carolina; Silvera-Ruiz, Silene M.; Ponce, Nicolás Eric; et al. (Frontiers in Immunology, 2023)
This work examines cellular immunity against SARS-CoV-2 in patients from Córdoba, Argentina, during two major waves characterized by different circulating viral variants and different social behavior. Using flow cytometry, we evaluated the main lymphocyte populations of peripheral blood from hospitalized patients with moderate and severe COVID-19 disease. Our results show disturbances in the cellular immune compartment, as previously reported in different cohorts worldwide. We observed an increased frequency of B cells and a significant decrease in the frequency of CD3 + T cells in COVID-19 patients compared to healthy donors (HD). We also found a reduction in Tregs, which was more pronounced in severe patients. During the first wave, the frequency of GZMB, CD107a, CD39, and PD-1-expressing conventional CD4 + T (T conv) cells was significantly higher in moderate and severe patients than in HD. During the second wave, only the GZMB + T conv cells of moderate and severe patients increased significantly. In addition, these patients showed a decreased frequency in IL-2-producing T conv cells. Interestingly, we identified two subsets of circulating CD8 + T cells with low and high CD8 surface expression in both HD and COVID-19 patients. While the percentages of CD8 hi and CD8 lo T cells within the CD8 + population in HD are similar, a significant increase was observed in CD8 lo T cell frequency in COVID-19 patients. CD8 lo T cell populations from HD as well as from SARS-CoV-2 infected patients exhibited lower frequencies of the effector cytokine-producing cells, TNF, IL-2, and IFN-γ, than CD8 hi T cells. Interestingly, the frequency of CD8 lo T cells increased with disease severity, suggesting that this parameter could be a potential marker for disease progression. Indeed, the CD8 hi /CD8 lo index helped to significantly improve the patient's clinical stratification and disease outcome prediction. Our data support the addition of, at least, a CD8 hi /CD8 lo index into the panel of biomarkers commonly used in clinical labs, since its determination may be a useful tool with impact on the therapeutic management of the patients.